ANALYSIS OF ONLINE LOAN PENETRATION AND CONSUMER BEHAVIOR IN INDONESIA - Sabrun Jusuf; Meykel Djuuna; Fricy Rumintjap (JURNAL ILMIAH EDUNOMIKA, 2026)
The development of financial technology (fintech) has driven the emergence of online lending services as an integral part of Indonesia’s digital financial ecosystem. While these services have the potential to expand financial inclusion, understanding of their penetration levels and consumer behavior patterns remains limited, particularly based on nationally scaled data. This study aims to analyze the penetration of online lending usage and consumer behavior in Indonesia based on generational groups, household expenditure levels, and primary reasons for usage. This research adopts a descriptive quantitative approach by utilizing secondary data from the 2025 Survey on Internet Penetration and User Behavior in Indonesia conducted by the Indonesian Internet Service Providers Association (APJII). The analysis is based on official percentage tables and infographics covering online lending usage status, user distribution by generation and expenditure level, as well as the motivations for using online lending services. The results indicate that the penetration rate of online lending in Indonesia remains relatively low, at approximately 8.21% of internet users. However, usage is concentrated within specific segments, particularly Generation Z and Millennials, as well as households with low to middle expenditure levels. Online lending is utilized for various purposes, with the main motivations including installment-based purchases without credit cards, fulfillment of urgent needs, and financing daily necessities, accompanied by factors such as promotional incentives, ease of process, and lifestyle considerations. These findings suggest that online lending functions, both as a consumption financing instrument and a short-term liquidity buffer. Overall, this study indicates that the primary users of online lending services are digitally adopt groups who simultaneously exhibit higher levels of financial vulnerability. These findings underscore the importance of strengthening targeted digital financial literacy initiatives and consumer protection measures in the development of the online lending ecosystem. This research is expected to serve as a foundation for policymaking and further studies that are more sensitive to generational dynamics and household expenditure structures within the context of Indonesia’s digital finance landscape.